Empirical correlations for the determination of R134a's convective heat transfer coefficient in horizontal and vertical evaporators having smooth and corrugated tubes - Dalkilic, A. S.; Celen, A.; Cebi, A.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Boiling heat transfer of R134a flowing in the inner tube and hot water flowing in the annulus were examined inside smooth and corrugated tube-in-tube heat exchangers in authors' previous studies experimentally. The apparatus has 0.85 m long double tube for vertical orientation and 2.5 m long double tube for horizontal orientation as its test sections whose inner ones are smooth and corrugated copper tubing having inner diameters of 0.0087 m for vertical tubes and 0.0081 m for horizontal tubes. The range of mass fluxes are 20,300 and 400 kg m(-2) s(-1) for vertical tubes, and 300, 400 and 500 kg m(-2) s(-1) for horizontal tubes. The average vapor qualities vary from 0.14 to 0.86 for vertical tubes, 0.09-0.81 for horizontal tubes, and saturation pressure interval is between 4.5 and 5.7 for both tube orientations. The average boiling heat transfer coefficient of R134a is calculated by means of the energy balance in the test section. In this existing study, the predictability of almost whole well-known empirical correlations in literature suggested for convective boiling flows in smooth and corrugated tubes is experienced by using the authors'large number of experimental database (302 data points for vertical tubes and 227 data points for horizontal tubes). Characteristics of trend lines plotted for the change of vapor quality, saturation temperature, mass flux and heat flux with experimental boiling heat transfer coefficients are examined as well in relation to various saturation temperatures and mass fluxes. Furthermore, the most successful correlations validated their predictabilities for both vertical and horizontal oriented evaporators having smooth and corrugated tubes. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Evaporator; Evaporation; Boiling; Corrugated tube; Calculating method; Heat transfer coefficient; GENERAL CORRELATION; DOWNWARD FLOW; CONDENSATION; ANNULI; FLUX; Thermodynamics; Mechanics